Sequestration of Zn2+ from aqueous solution using Klebsiella pneumoniae: Batch kinetics and continuous studies. (August 2016) - Majumder, Subhajit; Raghuvanshi, Smita; Gupta, Suresh
Abstract: The present study was aimed to isolate, Klebsiella pneumoniae from activated sludge. It was used to remove Zn 2+ from aqueous solution in batch and continuous modes. Batch study was conducted for 20–200 mg L −1 of initial Zn 2+ concentration to determine the optimum value of initial Zn 2+ concentration. Batch bioremediation studies were also performed to determine the optimum values of solution pH, minimal salt medium (MSM) dosage, macronutrients amount, aerobic & facultative anaerobic conditions, temperature and inoculum volume. The optimum solution pH for the growth of K. pneumoniae was found as 7 for the Zn 2+ bioremediation. The growth of K. pneumoniae was found optimum in aerobic condition and in the temperature range of 37–40 °C. In continuous mode, the removal of Zn 2+ from aqueous solution was investigated in a hybrid biofilter column packed with coal and compost as medium over a period of 60 days. K. pneumoniae was used as a potential metal removing agent. The maximum removal efficiency was obtained as 91.5% during phase II for 10 mL min −1 flow rate of Zn 2+ and 20 mg L −1 of Zn 2+ inlet concentration. Biofilter column was run under shock loading conditions for 14 days immediately after 60 days of operation which revealed the stable nature of the column with fluctuating inputs. Field emission scanning electron microscopy with electron dispersive X-ray (FESEM-EDX) analysis confirmed the presence of Zn 2+ and change in surface morphology after Zn 2+ sorption on the outer surface of K. pneumoniae .